2011
DOI: 10.3109/09546634.2010.551109
|View full text |Cite
|
Sign up to set email alerts
|

Combination effects of cosmetic moisturisers in the topical treatment of acne vulgaris

Abstract: Cosmetic moisturisers were applied to one side of the face of 18 male Japanese patients with acne vulgaris who were treated with a topical administration of adapalene and clindamycin phosphate gels. We assessed the alleviating effect of the moisturisers on the side effects of the treatment. The severity of acne and the number of inflammatory and non-inflammatory lesions were measured at 0, 2, and 4 weeks. The water content in the stratum corneum and transepidermal water loss were measured by comparing the mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…Moisturizers may be used for dry and irritated skin due to acne treatment and should be water‐based, non‐greasy, non‐comedogenic, non‐acnegenic and hypoallergenic. Moisturizers prevent treatment‐induced dryness and improve local tolerance to topical treatment (level of evidence, 1; strength of recommendation, A) . Moreover, moisturizers do not affect the efficacy of topical acne treatment, while improving stratum corneum water content and reducing the sensation of dryness .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moisturizers may be used for dry and irritated skin due to acne treatment and should be water‐based, non‐greasy, non‐comedogenic, non‐acnegenic and hypoallergenic. Moisturizers prevent treatment‐induced dryness and improve local tolerance to topical treatment (level of evidence, 1; strength of recommendation, A) . Moreover, moisturizers do not affect the efficacy of topical acne treatment, while improving stratum corneum water content and reducing the sensation of dryness .…”
Section: Discussionmentioning
confidence: 99%
“…Moisturizers prevent treatment-induced dryness and improve local tolerance to topical treatment (level of evidence, 1; strength of recommendation, A). 64,65 Moreover, moisturizers do not affect the efficacy of topical acne treatment, while improving stratum corneum water content and reducing the sensation of dryness. 62 These benefits were demonstrated in a study involving adapalene in which patients were randomized to receive either adapalene alone or adapalene in combination with a moisturizer.…”
Section: Recommended Skin Care For Acnementioning
confidence: 99%
“…The combined use of cosmetic moisturizer is reported to increase treatment adherence [14], and various other therapeutic modifications have been tried. Accordingly, the use of makeup does not appear to hinder acne treatments but actually improves patients' QOL [4].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that use of cosmetic moisturizers with adapalene and clindamycin gels significantly reduced the sensation of dryness and increased water content in the stratum corneum. Treatment efficacy was not diminished by use of moisturizers, and the authors recommended use of moisturizer plus topical treatment . In another Japanese study, Hayashi et al .…”
Section: Using Topical Retinoids In Skin Of Colormentioning
confidence: 99%
“…There is additional evidence besides the Thai study discussed above supporting the use of moisturizers with topical retinoid therapy in Asian patients. In Japan, Munehiro et al 63 demonstrated that use of cosmetic moisturizers with adapalene and clindamycin gels significantly reduced the sensation of dryness and increased water content in the stratum corneum. Treatment efficacy was not diminished by use of moisturizers, and the authors recommended use of moisturizer plus topical treatment.…”
Section: Positive Impact Of Moisturizers In Asian Skinmentioning
confidence: 99%